Recent Progress on the Production of Aluminum Oxide (Al2O3) Nanoparticles: A Review - Adzra Zahra Ziva; Yuni Kartika Suryana; Yusrianti Sabrina Kurniadianti; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (Universitas Muhammadiyah Magelang, 2021)
This study aims at discussing several methods to produce aluminum oxide (Al2O3) synthesis methods along with the advantages and disadvantages of each method used. In general, several methods are available: (1) precipitation, (2) combustion, (3) sol-gel, (4) wet chemical, (5) synthesis in supercritical water conditions, (6) microwave, (7) mechanochemical, and (8) hydrolysis, and the most efficient method for synthesizing Al2O3 is precipitation because it is facile and the simplest method (compared to other methods), can be proceeded using inexpensive raw materials, produces less pollution, and has several advantages: high purity product, high thermal stability, nearly homogeneous nanoparticle in size, and control desired particle size. The results of the study help to provide comparisons in producing various Al2O3 synthesis methods.